(untitled) (INNOVATIVE ECONOMY, 2026)
Gnatiuk T.M., Vasylyuk M.M., Shkromyda V.V., Sas L.S. ACCOUNTING AND ANALYTICAL INFORMATION AS THE INSTITUTIONAL BASIS OF THE KNOWLEDGE ECONOMY Purpose. The aim of the article is the theoretical and methodological substantiation of accounting and analytical information as the structural basis of the knowledge economy, disclosure of its potential in the processes of post-industrial transformation of society, and determination of strategic guidelines for the development of the accounting profession in the context of building a domestic knowledge ecosystem during the post-war recovery of Ukraine. Methodology of research. The institutional and systemic approaches are applied to substantiate accounting and analytical information as the institutional foundation of the knowledge economy. The historical-evolutionary approach and methods of abstraction are used to analyse the development of the accounting subject and to investigate the evolution of the perception of the specialist’s professional status as a dominant element of the institute of trust in the knowledge economy. The modelling method, structural-functional approach allowed revealing the newest functions of accounting (codification, protection, transmission), while causal analysis is applied to identify the institutional traps of the current regulatory standards regarding the expensing of research and development (R&D) costs, as well as to assess their impact on the capitalization of the innovative sector. Findings. It is proven that within the coordinates of the knowledge economy, accounting and analytical information transforms from a retrospective report into a key mechanism for generating trust in invisible assets. Its newest functions encompass the codification of tacit knowledge into digital assets, the protection of institutional memory, and the legitimization of the value of intellectual potential. It is established that the classical industrial accounting paradigm, based on the directive expensing of research and development (R&D) costs, creates institutional traps that misinform markets and artificially hinder the development of the knowledge economy. The necessity of integrating environmental, social, and human accounting in the digital XBRL/iXBRL format as an adequate tool for measuring knowledge-based effects is substantiated. It is revealed that the import of global industrial standards without local adaptation generates pseudo-institutional superstructures that distort the value of national intellectual wealth. Originality. The principles of institutional theory have been further developed through the identification of accounting information as an independent institutional basis that structures the space of trust. The evolutionary model of transforming the professional status of the accounting subject in accordance with the challenges of the knowledge economy has been improved. This is achieved through the conceptual substantiation of the inevitable transition to the institute of accounting guarantors, where the guarantor acts as a key architect of trust in the digital representation of intellectual capital, and digital ethics is defined as a new basic regulatory institution of the knowledge society. Practical value. The obtained conclusions and generalizations form the theoretical foundation for developing a national strategy for integrating the domestic financial reporting system into the global knowledge economy and post-industrial environment. The proposed concepts create a basis for the capitalization of business knowledge resources and can be implemented in the infrastructure design processes of Ukraine’s future post-war recovery and in training programs for accounting professionals capable of effectively managing intangible assets in the new economic reality. Key words: knowledge economy, accounting and analytical information, institutional theory, intellectual capital, accounting guarantor, digital reporting, knowledge asset, human capital.